Is the Time Necessary to Obtain Preoperative Stabilization a Predictive Index of Outcome in Neonatal Congenital Diaphragmatic Hernia? - Andrea Gentili; Rosina De Rose; Elisa Iannella; Maria Letizia Bacchi Reggiani; Mario Lima; Simonetta Baroncini (International Journal of Pediatrics)
Background. The study aims to verify if the time of preoperative stabilization (≤24 or >24 hours) could be predictive for the severity of clinical condition among patients affected by congenital diaphragmatic hernia. Methods. 55 of the 73 patients enrolled in the study achieved presurgical stabilization and underwent surgical correction. Respiratory and hemodynamic indexes, postnatal scores, the need for advanced respiratory support, the length of HFOV, tracheal intubation, PICU, and hospital stay were compared between patients reaching stabilization in ≤24 or >24 hours. Results. Both groups had a 100% survival rate. Neonates stabilized in ≤24 hours are more regular in the postoperative period and had an easier intensive care path; those taking >24 hours showed more complications and their care path was longer and more complex. Conclusions. The length of preoperative stabilization does not affect mortality, but is a valid parameter to identify difficulties in survivors’ clinical pathway.